Polypectomy of a Pedunculated Sigmoid Gastrointestinal Stromal Tumor : is that Feasible ? About a Case Report - Soua, Sabrine; Mohamed, Ghanem; Hallara, Olfa; Kchir, Nidham Eddine; Bouali, Mohamed Riadh (Archives of Clinical and Biomedical Research, 2023)
Gastrointestinal stromal tumors (GIST) are rare neoplasms that represent approximately 1–2% of gastrointestinal cancers. Colonic localization is very rare (5%). Treatment is based on surgery. In this case, we report a successful endoscopic resection of a small sigmoid GIST with conventional polypectomy in a 72-year-old woman.